Conformation and adsorption transition on an attractive surface of a ring polymer in solution. Issue 3 (5th December 2014) - Sheng, Junfang; Luo, Kaifu
Abstract : Ring polymers have the same critical adsorption point and crossover exponent as linear chains. Abstract : We investigate the effect of chain topology on conformation and adsorption transition on an attractive surface of a ring polymer in a dilute solution in a good solvent. Based on Flory theory, we find that the ratio of the mean squared radii of gyration of a ring polymer and a linear chain of identical length is 0.574, which is in good agreement with the results from renormalization theory, previous simulations and experiments. Using three-dimensional Langevin dynamics simulations, we examine the adsorption transition of a flexible ring polymer chain with one bead grafted to a flat solid surface and the conformation of the adsorbed chain. Compared with the linear chain, the ring polymer has the same critical adsorption point (CAP). At the CAP, the crossover exponent of the number of adsorbed beads with chain length is about 0.50 for both ring and linear chains. At the CAP, ring polymers are adsorbed on the surface more than linear chains, which agrees with experiments. In addition, we further observe that, compared with linear chains, the adsorption of ring polymers is faster. Under strong attractions, we observe that the exponent of the adsorption time as a function of the chain length is 1 + v 3D, where v 3D = 0.588 is the Flory exponent in three dimensions.